Comparative Law in a Changing World - Historical Reflections and Future Visions Fünftes Symposium der Juristischen Fakultät der Georg-August-Universität Göttingen mit der Yonsei Law School (Seoul) - Duttge, Gunnar (Universitätsverlag Göttingen, 2019)
In times of rapidly changing social worlds and an ever more fragile controllability of the law, international legal comparison obtains increasing relevance. Frequently, similar or even identical questions and problems must be answered and solved in different legal communities, but there is rarely a single answer or solution. For a decade, the Faculty of Law of the University of Göttingen and the Yonsei Law School in Seoul (Republic of Korea) have engaged in continuous dialogue about both current and fundamental questions of legal reform. In October 2018, the fifth German-Korean Symposium took place. The lectures and presentations covered highly relevant aspects of public environmental law, insolvency proceeding, law of criminal sanctions and law of the constitution of the criminal courts as well as computer crime, including historic and philosophical foundations of the law. This volume combines the elementary contributions and makes them accessible for the interested professional public.